Histologic Changes During Treatment With Vismodegib in Locally Advanced Basal Cell Carcinoma: A Series of 19 Cases. (October 2019) - Bancalari, B.; Llombart, B.; Serra-Guillén, C.; Bernia, E.; Requena, C.; Nagore, E.; Traves, V.; Calomarde, L.; Diago, A.; Guillén, C.; Sanmartín, O.
Abstract : Background: There are no large series describing cutaneous histologic changes during treatment with vismodegib in locally advanced basal cell carcinoma (BCC). Objective: To analyze histologic changes in skin biopsy specimens from patients with locally advanced BCC treated with vismodegib. Methods: A descriptive, retrospective study of patients with locally advanced BCC treated with vismodegib between June 2012 and December 2017 at the Instituto Valenciano de Oncología, Spain. Nineteen patients were biopsied before and during the treatment with vismodegib, and we compared histologic changes observed. Results: Seven patients (37%) achieved complete response, which was characterized by replacement of tumor stroma with a hyaline scar, lymphocytic inflammatory infiltrate, keratin formation, and infundibular cysts. Twelve patients (63%) achieved partial response; 5 showed no phenotypic changes, whereas 7 showed histologic changes; 5 cases showed metatypical differentiation; and 2 cases presented squamous differentiation. We observed no cases of squamous cell carcinoma arising at vismodegib treatment sites and no association between initial histologic subtype and clinical response. Limitations: Many biopsy specimens were obtained by punch biopsy and may not be representative of the full tumors. We studied histologic changes only in complete and partial responses. Conclusion: Vismodegib can induce histologic changes toward metatypical or squamous differentiation of BCC in patients with partial response. Keratinizing phenomena were frequent, both in partial and complete response groups.